Deposition and characterization of metal doped diamond like carbon (Me(Ti, Nb)-DLC) films - Uğur, Deniz. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In today’s world, sustainable development and green technology concepts are pronounced more than ever, which force tighter efficiency measures and implementation of energy saving solutions to every applicable system. Wear and friction causing a significant loss of energy and material, is the foremost important source of efficiency loss. This thesis study was conducted to deposit hard, wear resistant and low friction coefficient thin films on high speed steel substrates to reduce friction and wear. This purpose was accomplished by the growth of diamond like carbon films (DLC) doped with titanium and niobium, by pulsed-dc closed field unbalanced magnetron sputtering (CFUBMS) method. Resulting coating characterizations were carried out in four different aspects, such as; the structural characterization was composed of scanning electron microscopy (SEM) and surface roughness studies, compositional characterization was composed of x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS) studies, tribological characterization was composed of pin on disc (POD) and adhesion scratch tests and finally, hardness characterization was composed of micro and nanohardness measurements. Resulting coatings presented a dense structure, accompanied with slight columnar growth and were seen to have moderate friction values, high wear resistance and high hardness.
Keywords: Carbon -- Mechanical properties.